SHAMANISME: FENOMENA RELIGIUS DALAM SENI PERTUNJUKAN NUSANTARA - -, Sunarto (Harmonia: Journal of Arts Research and Education, 2013)
Budaya Shamanisme ini telah memberikan kepada Nusantara musik ritual dengan waditra: gendang, gong, dan kecrek; dengan pertunjukan yang mempunyai maksud untuk memuliakan arwah para leluhur. Bentuk seni yang ditampilkan, seperti: tari topeng. Budaya ini juga telah membawa skala Pentatonik yang berasal dari tradisi Melayu-Nusantara untuk wilayah belahan barat, dan tradisi Asiatik untuk belahan Timur. Hal tersebut mirip dengan paham Cina kuno (3500 SM), yang memandang musik sebagai seni yang mengungkapkan persatuan sorga dan bumi. Konsep seni adhiluhung (yang berarti damai dan agung) dalam Gamelan Jawa diturunkan dari paham tersebut. Sedangkan dalam Hinduisme menganggap musik sebagai Yoga untuk bersatu dengan Brahman dan sarana pengembangan rasa estetis-religius. Suhardjo Parto dalam Disertasinya, Folk Traditional as a Key to the Understanding of Music Cultures of Java and Bali (Osaka University, 1990), membuat peta dengan sebutan wilayah etnomusikologis âIndonesia Barat Dayaâ: suatu wilayah yang terbentang dari Sumatra Selatan, Jawa (Madura), Bali, dan Lombok.Â This Shamanism culture has given the archipelago music: ritual music of waditra: drums, gongs, and kecrek; with performances that had the intention to honour deceased ancestors. The form of the performance art shown is Tari Topeng (mask dance). This culture has also brought a pentatonic scale derived from the Malay-Indonesian tradition in the Western hemisphere to Asiatic tradition in the Eastern hemisphere. It is similar to ancient China concept (3500 BC), which looked at music as an art that expresses the unity of Heaven and Earth. This is from which the concept of art adhiluhung (peaceful and great) in Javanese Gamelan is derived. Hinduism considers music as Yoga for uniting with Brahman and a means of developing a sense of the aesthetic-religious. Suhardjo Parto in his dissertation, Traditional Folk as a Key to the Understanding of Music Cultures of Java and Bali (Osaka University, 1990), made a map as the ethnomusicologist âSouthwest Indonesiaâ: an area stretching from South Sumatra, Java (Madura), Bali, and Lombok.